Stories of an "other" Caribbean: monstrous and dystopian simulations in recent cinema and narrative works (Ogigia. Revista Electrónica de Estudios Hispánicos, 2019)
The monstrosity and dystopia of Caribbean bodies, behaviors and spaces will be analyzed in relation to the literature of Dominican writers Rita Indiana Hernández and Frank Baez, as well as the recent Cuban film directed by Alexander Brugués. The emphasis will be on how these aesthetic objects -mainly of abject and grotesque nature, and configured by both audiovisual and narrative strategies- represent an "other" Caribbean which resists the exotic cliché while at the same time legitimizing the foundational discourse of violence and brutality.
Keywords: Representations of the Caribbean; Monstruosity; Dystopia; Degeneration; Horror; Violence; Parody